I rapporti tra i coniugi nel pensiero dei Padri della Chiesa (I-III sec.) - Mazzucco, Clementina (Augustinianum, 2014)
The article deals with the views of the Fathers of the Church on relations between husband and wife between the end of the first century and the end of the third century, an age that is less studied in this respect, even though it offers good documentation concerning the subject (particularly in the case of Tertullian and Clement of Alexandria). Four themes are considered: 1. adultery and separation; 2. the conjugal debt; 3. the division of tasks between husband and wife; 4. the faith life of the couple. Different opinions and often original points of view are presented in regard to the lawfulness of the second marriage, the culpability of adultery, the value of sexuality in the marriage and the wife’s subordination to her husband.